Karakteristik Fluida Hidrotermal Endapan Emas Orogenik di Pegunungan Rumbia, Kabupaten Bombana, Provinsi Sulawesi Tenggara - Hasria, Hasria; Idrus, Arifudin; Warmada, I Wayan (Jurnal Geologi dan Sumberdaya Mineral, 2019)
Recently, gold exploration activities  are not only focused along volcanic-magmatic belt but also starting to shift along metamorphicand sedimentary terrains. The purpose of this study is to analyses the characteristics hydrothermal fluids gold deposits t in the Rumbia Mountains, Bombana Regency, Southeast Sulawesi. There are three generations of veins identified including the first is parallel to the foliations, the second crosscuts the first generation of veins/foliations, and the third is of laminated deformed quartz+calcite veins at the late stage. Temperature of homogenization (Th) and salinity at Rumbia Mountain of the first vein vary from 220 to 355.30oC and 6.74 to 10.11 wt. % NaCl eq., respectively. The second generation vein was originated at Th of 157 to 255.50oC and salinity of 3.39 to 6.88 wt.%NaCl eq., whereas the third generation vein formed at lowest Th varying from 104.40 to 265.90oC and less saline fluid at salinity range between 0.18 and 6.30 wt.% NaCl eq. The result of temperature formation value correlation to the depth of the formation of orogenic gold deposits in Rumbia Mountain is indicated to form on sub-greenschist to greenschist facies at depth of about 4-8 kilometers and formation temperature between 104.40 - 355.30oC at zone epizonal and mesozonal. Based on characteristics fluids inclusion discussed above, the primary metamorphic-hosted gold mineralization type at Rumbia Mountain tends to meet the criteria of orogenic gold type.  Keyword : fluid iclusion, quartz veins, Rumbia mountain, orogenic gold deposits.